(untitled) (Research, Society and Development, 2023)
This study sought to analyze the physical and mechanical characteristics of mixtures of soil and construction and demolition waste. For this, mixtures of recycled soil and construction waste were prepared at concentrations of 15% and 30% in relation to the dry weight of the soil. Soil samples were collected in Bairro Jardim Imperial, in the city of Cuiabá/MT and classified by the Transportation Research Board-TRB classification system as A6. According to the classification by the expeditious MCT methodology (Miniature, Compacted, Tropical), it is a non-lateritic silty soil. The recycled aggregate was donated by the recycling plant of the company Eco Ambiental located in the capital of Mato Grosso. With the results of the California Bearing Ratio (CBR) tests, it was observed that the mixture of recycled aggregates with the soil showed an increase in the CBR value and a reduction in expansion, promoting an improvement in the parameters. However, this improvement has not yet met the necessary requirements for strengthening the subgrade, and it is necessary to correct the expansion of the mixtures.